Petrogênese das rochas vulcânicas do Complexo Morro Redondo (PR-SC), Província Graciosa, Sul do Brasil - Silva, Genilson Ribeiro da (2021)
The S-SE region of Brazil, between the states of São Paulo and Santa Catarina, is marked by the occurrence of an intense Neoproterozoic volcano-plutonic activity, formed during the post-collisional stages of the Brasiliano orogeny. The rocks are predominantly silicic, have chemical signatures of type-A granites and rhyolites and form several granitic and syenitic plutons (Graciosa Province), as well as effusive and explosive volcanic sequences in contemporary volcano-sedimentary basins. Additionally, the silicic volcanics in these basins are commonly part of a bimodal volcanism, with scarcity of intermediate lithotypes. Among these occurrences, the Morro Redondo Complex (PR-SC) is particularly interesting because it encompasses two type-A granitic plutons with contrasting geochemical affinities (peralkaline and peraluminous), along with comagmatic silicic and basic volcanics and subvolcanics. This work presents an integrated study of the Morro Redondo volcanic rocks based on (1) petrographic, (2) lithochemical, (3) geochronological (zircon U-Pb) and (4) isotopic (zircon Hf-O) data. The results show that the basic volcanics and subvolcanics correspond to alkali-basalts and microgabbro/microdiorites with pigeonite/augite and andesine/labradorite. On the other hand, the silicic rocks are predominantly alkali-feldspar rhyolites and granophyres with high SiO2 contents (>70 wt.%) and low magnetic susceptibilities. Two subgroups of rhyolites have been identified: (1) aluminous rhyolites, with biotite ± hornblende and metaluminous to peraluminous affinity, compositionally equivalent to the Quiriri granites; and (2) alkaline rhyolites, with sodic amphiboles and clinopyroxenes and metaluminous to peralkaline affinities (comendites), chemically similar to the Papanduva granites. In-situ zircon U-Pb dating (LA-ICP-MS) of an aluminous rhyolite indicate crystallization ages around 585±5 Ma that overlap within error with the ages of the Morro Redondo granites (580±5 to 578±3 Ma), as well as with the ages of volcanic episodes in volcano-sedimentary basins of S-SE Brazil. Additionally, zircon Hf-O isotopic signatures for this rhyolite indicate εHf values between -23.6 and -16.7 (with TDM model ages between 2.72 and 2.34 Ga) and δ 18O = 5.0±0.1‰. The petrogenetic model proposed for the origin of the Morro Redondo volcanics starts with the partial melting (~13%) of an enriched mantle (EM-1 type) in an extensional post-collisional environment, with the production of basaltic magmas. These in turn would have promoted the partial fusion of the basement rocks (Luiz Alves Microplate) generating A-type magmas that ascended to shallow crustal levels, evolving by fractional crystallization (45-52%) to compositions akin to the aluminous granites of the Quiriri Pluton. From this "reservoir", subsequent processes of fractional crystallization (30-50%) mainly of alkali feldspar, gave rise to more peralkaline compositions (Papanduva Pluton). Finally, rhyolites were extracted from these crystalline mushs, ascending to the surface as dikes.